5 Comments »

  1. solution
    a, b, and c represent current ages of three friends
    three years ago, the equation of average would look like this;
    ((a+b+c)-9)/3=27;
    (a+b+c)=72………..(1)simplified
    average of two friends five yrs ago:
    ((a+b)-10)/2=20
    (a+b)=50……………(2)simplified
    therefore
    (50+c)=72…………(3) derived
    hence from equ. 3, c=22
    the age of the third person is 22 years.

    Like

  2. nope…

    You can check this solution:
    3 years ago the sum of their (Rajan, Rakesh and Mukesh) ages was: 27 x 3 = 81 years
    • The sum of their present ages is: 81 + 3 + 3+ 3 = 90 years…………….(1)
    • 5 years ago the sum of ages of Rakesh and Mukesh was: 20 x 2 = 40 years
    • So sum of present ages of Rakesh and Mukesh is: 40 +5 +5 = 50 years…………(2)
    • The difference of 1 and 2 equation gives the present age of Rajan.: 90 – 50 = 40 years

    Like

  3. solution-modified
    a, b, and c represent current ages of three friends
    three years ago, the equation of average would look like this;
    ((a+b+c)-9)/3=27;
    (a+b+c)=90………..(1)simplified
    average of two friends five yrs ago:
    ((a+b)-10)/2=20
    (a+b)=50……………(2)simplified
    therefore
    (50+c)=90…………(3) derived
    hence from equ. 3, c=40
    the age of the third person(Rajan) is 40 years.

    Like

Leave a Reply

Please log in using one of these methods to post your comment:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s